An unusual case of CTEPH treated by BPA in a patient with a single lung after cancer surgery. (27th May 2022) - Darocha, Szymon; Kurzyna, Paweł; Banaszkiewicz‐Cyganik, Marta; Kędzierski, Piotr; Florczyk, Michał; Pietrasik, Arkadiusz; Zieliński, Dariusz; Biederman, Andrzej; Torbicki, Adam; Kurzyna, Marcin
Abstract: A 46‐year‐old man 1 year after left‐sided pneumonectomy for squamous cell lung cancer presented with severely limited exercise tolerance and dyspnea corresponding to World Health Organization functional class IV (WHO Class IV). After right heart catheterization (RHC), mean pulmonary artery pressure (mPAP) was 43 mmHg and pulmonary vascular resistance (PVR) was 10.2 Wood units (WU). Arteriography revealed organized clots located at the proximal level of the right pulmonary artery, leading to a diagnosis of chronic thromboembolic pulmonary hypertension (CTEPH). The CTEPH team disqualified the patient from surgical treatment due to high perioperative risk and referred him for balloon pulmonary angioplasty (BPA) together with pulmonary hypertension‐specific pharmacotherapy (sildenafil). The patient underwent a cycle of nine BPA sessions and completed treatment without complications. Follow‐up showed sustained hemodynamic improvement in RHC (mPAP 23 mmHg, PVR 2.6 WU), improved physical capacity (WHO Class II), and relief of dyspnea symptoms.